Factors Affecting Urban and Rural Household Electricity Demand in South Sulawesi Province, Indonesia - Romadhoni, Buyung; Akhmad, Akhmad; Ansaar, Ansaar; Alam, Syamsul; Mauliana, Deasy (International Journal of Energy Economics and Policy, 2025)
This study aims to analyze the factors influencing household electricity demand in urban and rural areas of South Sulawesi Province. The seven independent variables used in this study include electricity price, household income, number of family members, electronic device ownership, education level, number of rooms, and a dummy variable for urban-rural areas. The analysis method used was multiple linear regression with a quantitative approach based on data from 400 household respondents. The results show that household income, number of family members, electronic device ownership, number of rooms, education level, and the dummy variable for urban-rural areas have a positive and significant effect on electricity consumption. Conversely, electricity price has a significant negative effect. This finding indicates that household economic and physical characteristics are more important determinants of electricity demand than social factors. This study recommends electricity tariff policies tailored to household socioeconomic conditions and improved energy access and education, especially in rural areas.